A comprehensive analysis of gastroesophageal reflux disease: Pathophysiology, clinical manifestations, and diagnostic approaches - Al-Arej, Ibrahim Muhammad; Alsayegh, Abdullatif Suliman; Al Owias, Meshal Ibrahim Zaid; Aldawsari, Hamad Fahad Hamad; Alanezi, Bader Sayah; Al-Shuwayman, Abdullah Abdulrahman (International journal of health sciences, 2020)
Background: Gastroesophageal reflux disease (GERD) is a common condition characterized by the reflux of stomach contents, leading to troublesome symptoms and potential complications. The Montreal definition emphasizes symptom severity, while the Lyon Consensus focuses on physiological aspects, and the Rome IV Conference highlights functional syndromes resembling GERD. This article aims to provide a comprehensive analysis of GERD, consolidating various definitions and perspectives. Aim: The study seeks to clarify the multifaceted nature of GERD, including its pathophysiology, clinical manifestations, diagnostic approaches, and therapeutic strategies. Methods: This narrative review synthesizes existing literature, examining prevalence, morbidity, and mortality associated with GERD, as well as its pathogenesis and the impact of lifestyle factors such as obesity. Data from various studies were analyzed to assess the global prevalence of GERD and its complications. Results: GERD prevalence varies globally, from 2.5% in China to 51.2% in Greece, with significant associations between obesity and GERD-related complications, including esophageal adenocarcinoma (EAC). The economic burden of GERD is substantial, with significant healthcare costs reported in multiple countries. The review also highlights the dual role of Helicobacter pylori, which may both exacerbate and protect against GERD symptoms.